New technologies for carbon-ion radiotherapy — Developments at the National Institute of Radiological Sciences, QST, Japan. (September 2019) - Kanematsu, Nobuyuki; Furukawa, Takuji; Hara, Yousuke; Inaniwa, Taku; Iwata, Yoshiyuki; Mizushima, Kota; Mori, Shinichiro; Shirai, Toshiyuki
Abstract: The National Institute of Radiological Sciences in Japan started clinical studies of carbon-ion radiotherapy (CIRT) in 1994. Due to the high linear energy transfer (LET) of highly charged particles, carbon-ion beams show high relative biological effectiveness in cell killing, especially at the Bragg peak of dose near the beam range, which is controlled to conform to a tumor. Recent technological developments for CIRT include fast pencil-beam scanning, fluoroscopic respiratory motion management, advanced beam modeling for treatment planning, and a superconducting rotating gantry, which have contributed to accuracy, precision, and conformation of dose, operational efficiency, and patient comfort. With technological maturity, CIRT facilities are rapidly increasing in Asia and Europe. Ongoing developments include extension to multiple ion species and facility downsizing to raise the quality and availability of ion-beam therapy in medical care.